Collapse of a nonductile concrete frame Shaking table tests. - Wu, Chiun-lin (Earthquake engineering & structural dynamics.)
Post-earthquake reconnaissance has reported the vulnerability of older reinforced concrete (RC) columns lacking details for ductile response. Research was undertaken to investigate the full-range structural hysteretic behavior of older RC columns. A two-dimensional specimen frame, composed of nonductile and ductile columns to allow for load redistribution, was subjected to a unidirectional base motion on a shaking table until global collapse was observed. The test demonstrates two types of column failure, including flexure-shear and pure flexural failure. Test data are compared with various simplified assessment models commonly used by practicing engineers and researchers to identify older buildings that are at high risk of structural collapse during severe earthquake events. Comparison suggests that ASCE/SEI 41-06 produces very conservative estimates on load?deformation relations of flexure-shear columns, while the recently proposed ASCE/SEI 41-06 update imposes significant modifications on the predictive curve, so that improved accuracy has been achieved.